OP0073 Polymorphisms in the FCN1 Gene Coding for M-Ficolin are Associated with Disease Activity, Radiographic Damage and are the Strongest Predictors of DAS28 Remission in 180 DMARD Naive Early Rheumatoid Arthritis Patients. (9th June 2015) - Ammitzbøll, C.G.; Steffensen, R.; Thiel, S.; Jensenius, J.C.; Hørslev-Petersen, K.; Ellingsen, T.; Hetland, M.L.; Junker, P.; Østergaard, M.; Stengaard-Pedersen, K.
Abstract : Background: M-ficolin is a pattern recognition molecule that collaborates with associated serine proteases as an activator of the complement system. High M-ficolin levels are strongly associated with high disease activity in early RA and low levels at baseline are strong predictors of both remission and low disease activity after one year (1). Single nucleotide polymorphisms (SNPs) in the M-ficolin gene FCN1 have been shown to influence the concentration and function of M-ficolin (2) and are associated with outcome in patients with systemic inflammation. Objectives: To investigate the associations of 7 FCN1 SNPs with DAS28, modified Total Sharp Score (mTSS), low disease activity (LDA, DAS28<3.2), and remission (DAS28≤2.6) in a cohort of 180 early RA patients. Methods: 180 DMARD naïve RA patients with disease duration <6 months were included in a randomized double blind placebo-controlled trial (OPERA-study, NCT00660647 ) of methotrexate, intra-articular glucucorticoids plus either adalimumab or placebo (3). SNPs were analyzed with TaqMan OpenArray system (2). The associations between SNPs and endpoints were evaluated using linear or logistic regression analysis adjusted for age, sex, anti-CCP and treatment, with the common allele homozygous genotype selected = "selected" as reference. Results: Baseline characteristics were similar in the two groups, table 1 . Table 2 states the four SNPs of which the minor allele was previously shown to be associated with higher plasma M-ficolin levels in healthy adults (2). Homozygosity of the minor allele in any of these 4 SNPs was associated with higher DAS28 at both baseline (p<0.005) and after one year of aggressive treatment (p<0.009), while no effect was observed in the heterozygote state. Homozygosity of the minor allele in the 4 SNPs was further associated with increased mTSS at both baseline (p<0.02) and at year one (p<0.04), except for rs7657015 (p=0.06). The four SNPs were, in multivariate logistic regression analyses, the only variables able to predict LDA at year one (OR between 0.16 to 0.18) and the strongest predictors of remission (OR between 0.24 to 0.26) followed by treatment with adalimumab (OR between 2.49 to 2.66). Conclusions: Homozygosity of the minor allele of 4 FCN1 SNPs is associated with higher DAS28 levels and modified Total Sharp Score in early RA. The four SNPs were the only variables capable of predicting LDA and the strongest predictors of DAS28 remission. These data consolidate our previous findings that M-ficolin, a molecule of the innate immune system, is a strong prognostic marker at both the protein and gene level. References: Arthritis Rheum.2013 Dec;65(12):3045-50. PLoS One.2012;7(11):e50585 Ann Rheum Dis. 2014 Apr;73(4):654-61. Acknowledgements: The authors would like to thank all participating patients, study nurses and coinvestigators Disclosure of Interest: None declared